Impact of obesity on myocardial microvasculature assessed using fully-automated inline myocardial perfusion mapping CMR. (8th February 2021) - Joy, G; Crane, JD; Lau, C; Augusto, J; Brown, LAE; Chowdhary, A; Kotecha, T; Plein, S; Fontana, M; Moon, JC; Kellman, P; Xue, H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Guy"s and St Thomas" Charity University College London Hospitals Biomedical Research Centre Background: Obesity and cardiovascular disease are associated, but the relationship is poorly understood. Myocardial perfusion, metabolic derangement and lipotoxicity appear adversely associated in many scenarios (myocardial injury, diastolic dysfunction, diabetes). Altered perfusion (by PET) predicts outcome, and it is hypothesised that perfusion derangement is part of causality for cardiac disease and adverse outcomes. Purpose: To assess the presence and pattern of myocardial microvascular dysfunction in patients with obesity (scheduled for bariatric surgery) using stress quantitative perfusion mapping. Methods: 38 subjects with obesity planned to undergo bariatric surgery and 38 age and sex matched healthy volunteers (no diabetes, no hypertension) underwent anthropometry, biochemistry and CMR at 1.5T (Siemens) with cine imaging, stress (adenosine 140-210 mcg/kg/min) and rest fully-automated quantitative perfusion mapping. Results: Bariatric patients had a higher BMI (44 ± 6.4 vs 26.5 ± 4kg/m2 p = 0.001); 58%(22) were diabetic and 58%(22) had hypertension. Bariatric patients had higher absolute but lower indexed end-diastolic volumes, and overall higher ejection fractions (+5%) (see Table). Rest myocardial blood flow (MBF) in bariatric patients was the same (1.00 ± 0.3 vs 0.88 ± 0.24 p = 0.052), but stress perfusion results were significantly lower both for stress MBF (2.35 ± 0.69 vs 2.93 ± 0.76ml/g/min p = 0.001) and myocardial perfusion reserve (MPR 2.48 ± 0.82 vs 3.4 ± 0.81ml/g/min p = 0.0001). Although this was transmural, the endocardial stress MBF was particularly negatively affected in the bariatric cohort compared to controls (endocardial MBF 2.16 ± 0.65 vs 2.82 ± 0.73ml/g/min, p = 0.0001 vs epicardial MBF: 2.52 ± 0.76 vs 3.06 ± 0.79 p = 0.003), meaning there was an increased endo-epicardial stress MBF gradient in bariatric patients (0.87 ± 0.12 vs 0.92 ± 0.07 p = 0.03). Conclusion: Compared to healthy controls, patients with obesity have abnormal myocardial stress perfusion with reduced global perfusion, perfusion reserve and an increased transmyocardial perfusion gradient.